Maternal and fetal outcome in patients with gestational diabetes mellitus - Kumar, Vinay; Dogra, Anju (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Women with gestational diabetes mellitus (GDM) are expected to have increased risk for the development of gestational hypertension or pre-eclampsia. GDM is associated with an increased risk of maternal and fetal complications. Aims and objectives were to study the maternal and fetal outcome in patients with GDM. Methods: A retrospective cohort study was conducted in SMGS hospital, GMC Jammu over a period of nine months from January 2020 to September 2020. A total of 278 patients were recruited in the study and divided into two groups group A consists of 139 patients with GDM and group B comprises 139 patients without GDM. Maternal and neonatal complications were noted. Results: The women with GDM had higher BMI. The 18% of the women had BOH. The 315 had associated hypertension. The 56% women with GDM had vaginal delivery as compared to 77% in women without GDM. Shoulder dystocia was reported in 2% women in GDM group, while no case was reported in another group. The 18% of the neonate born to mother with GDM required NICU admission and 4 fetal death were reported, while no fetal death was reported in another group. Conclusions: Early screening for gestational diabetes especially in high risk patients should be done for a better maternal and neonatal outcome. Pregnant women with GDM should deliver at health facilities to properly manage any complication if occurs during delivery.